A Service Model for 6LoWPAN Wireless Sensor Networks - Xiaonan Wang; Haili Huang (International Journal of Distributed Sensor Networks)
This paper proposes a 6LoWPAN service model based on the IPv6-based k -Anycast communication model. This model is extended into 6LoWPAN service model so that the data-centric services of WSN can be achieved efficiently in the address-centric 6LoWPAN. In the proposed service model, an IPv6 node can obtain multiple network services through one request-response interaction where multiple sensor nodes cooperate to complete all requested network services and they provide their respective network services at the same time. As a result, the delay time is shortened. In addition, the proposed service model avoids the service failure caused by dormant sensor nodes. Since users can only request the network services they are interested in, the redundant data transmission is avoided. The performance parameters of the proposed service model are analyzed, and the data results show that the performance of the proposed service model is better.